2015
DOI: 10.1111/joms.12135
|View full text |Cite
|
Sign up to set email alerts
|

Less is More, or Not? On the Interplay between Bundles of Slack Resources, Firm Performance and Firm Survival

Abstract: Although a significant body of research has investigated the independent effects of distinct types of slack resources, current theoretical and empirical work does not sufficiently clarify how bundles of slack resources affect firm outcomes. Drawing on the resource constraints literature and the slack literature, we investigate how distinct bundles of financial and human resource slack influence firm performance and survival. Using a sample of 4715 European information and communication technology firms, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 97 publications
(179 reference statements)
1
93
0
4
Order By: Relevance
“…On the other hand, some scholars have stated that, limited by having fewer resources, firms are forced to innovate, particularly in a competitive environment (Baker & Nelson, 2005;Paeleman & Vanacker, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, some scholars have stated that, limited by having fewer resources, firms are forced to innovate, particularly in a competitive environment (Baker & Nelson, 2005;Paeleman & Vanacker, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fussler and James (1996) first defined environmental innovation as a new type of innovation that could help to reduce environmental damage and to create business value for firms at the same time. Some researchers have proposed that the appropriate amount of slack resources can help an organization to adapt to a rapidly changing environment, and to execute timely strategic adjustment and change (Azadegan, Patel, & Parida, 2013;Lee, 2011;Parida & Örtqvist, 2015), while others have suggested that organizations should reduce slack resources to minimize operational costs (Baker & Nelson, 2005;Paeleman & Vanacker, 2015). Specifically, environmental innovation refers to new products, processes, systems, services and procedures that aim to reduce the consumption of resources and environmental pollution (Cheng, Yang, & Sheu, 2014;Reid & Miedzinski, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forms of slack, such as financial, operational, and human resource, were also identified for the additional tests. Human resource slack was most commonly measured by the ratio of numbers or cost of employees to firm sales or assets (Lecuona and Reitzig, ; Mishina et al, ; Paeleman and Vanacker, ; Vanacker et al, ), but sometimes also measured by the ratios of specific groups of employees within the firm (Powell, ; Voss et al, ). Following Voss et al’s () conceptualization of operational slack as unused or underutilized operational resources, we classified operational slack into capacity‐related expenses (e.g., SG&A and inventory) or PPE, often relative to sales or assets (Hendricks et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Organizational slacks include financial and human resource slacks [17]. Prior research [18,19] has focused on slack in these two resources, which are closely related to firms' emergence and development. Financial slacks usually represent unabsorbed slack that is currently uncommitted and available for redeployment [19], such as cash and receivables that are highly flexible and can be disbursed on managerial discretion.…”
Section: Introductionmentioning
confidence: 99%